Use of Biopolymers for Chelating Agents in the Synthesis of Magnetic Cobalt Ferrite Nanoparticles - Hunyek, Anuchit (Journal of Advanced Development in Engineering and Science, 2023)
The three types of biopolymer consist of corn starch tapioca starch and aloe vera gel were studies for using as chelating agent in the synthesis of magnetic cobalt ferrite nanoparticles (CoFe2O4) by sol-gel method. The samples were obtained from sol-gel reaction until completely dry. Appropriate calcine temperature range were selected by TGA technique analysis, found that it was temperature range of 600-800 OC. The cobalt ferrite phase was proved by XRD technique. The XRD patterns showed peak of cobalt ferrite phase from some chelating agents. The crystallite size can be calculated by Scherrer’s equation. The range of crystallite size was 28 - 30 nm. The morphologies obtained from the SEM image showed clustering. The size distribution can be analysis by LPSA, found that, the size distribution was relatively wide when using corn starch. Hysteresis loops were measured by VSM technique showed high saturated magnetization for the use of tapioca starch. Likewise, the coercive field and squareness have been altered by influence of chelating agent types.